Technology transfer between universities and companies: Two cases of Brazilian universities - Chais, Cassiane; Ganzer, Paula Patrícia; Olea, Pelayo Munhoz (Innovation & management review, 2018)
Purpose: This paper aims to research how technology transfer occurs, based on the Schumpeterian approach to innovation trilogy focusing on the interaction between the university and the company. Design/methodology/approach: The methodology used for this study was the analysis of two cases with an exploratory and qualitative approach. The case study subjects were two Brazilian universities: University of Campinas (UNICAMP) and University of Vale do Rio dos Sinos (UNISINOS). Semi-structured interviews were used as the data collection technique, whereas content analysis was used as the analysis technique. Findings: The main results showed the need of companies and universities to understand that working in collaborative technology research contributes to the transformation of applied research into technological innovations that can transform society. Research limitations/implications: The research's limitations were the unfeasibility of studying the government helix, the lack of clear and established processes within universities so that a comparison between the cases would be possible and the lack of access to technology contracts, as they are considered confidential. In addition, the use of two cases is considered a limitation, as it is not possible to generalize the conclusions pointed out by the study. Originality/value: With this research, the authors were able to conclude that the university-industry interaction process has been improving, but it still needs to advance in organizational aspects. Some of the aspects to be considered are the adjustments for the institutions' internal policies, the existing negotiations, the researchers' behavior regarding the dissemination of the innovation culture and the performance of the technological innovation centers, which gradually are being trained to work in the market as well as in the university. It is necessary that primarily companies and universities understand that they must join efforts in collaborative technological research, so that the financial resources invested are not only accepted as published articles in qualified journals but also turn into technological innovations accepted by the market. All this investment must return as new products, services and technologies that generate local, regional, national and even international impact, implementing new types of businesses and new markets and yielding an economic impact in the country, thus generating innovation and social well-being.